If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3z + -8(2z + y) = 0 Reorder the terms: -3z + -8(y + 2z) = 0 -3z + (y * -8 + 2z * -8) = 0 -3z + (-8y + -16z) = 0 Reorder the terms: -8y + -3z + -16z = 0 Combine like terms: -3z + -16z = -19z -8y + -19z = 0 Solving -8y + -19z = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '19z' to each side of the equation. -8y + -19z + 19z = 0 + 19z Combine like terms: -19z + 19z = 0 -8y + 0 = 0 + 19z -8y = 0 + 19z Remove the zero: -8y = 19z Divide each side by '-8'. y = -2.375z Simplifying y = -2.375z
| -57+5x=-x+45 | | 49-k=19 | | 2x-5(x-3)=-4+2x-6 | | -4x^2-6x=192 | | 90=n+n-3 | | 4(2a+30)=5(a+144) | | -7x-19=51 | | 90=x+20+x | | -4(y+2)=-9y+2 | | 8(t-2)+7t=5(3t+3)-9 | | 2(2.5-9)+6b=14 | | 2(4x+3)-2x=4+3x | | 5x-4(-1x-3)=8 | | 1.00x+100=2.50x | | 4x+17+4x-39=90 | | 2b+3(b-2)=9 | | 6x-6+3x=-6 | | 8x-4=6x+x+9 | | 3(2x-15)-x=65 | | 1.00x+100=2.50 | | 7x-9-x=3 | | -32-4x=16 | | 7y-7=3+1 | | -8x-6+2x=12-4x | | 2x+5x+20=2x+3 | | 1.00x*100=2.50x | | -3(n-14)=56-n | | 1.00x*100=2.50 | | 2=-14x | | -(6x-5)+4x-6=-1 | | 6x+8x-21=84-7x | | -0.8x-0.6+0.2x=12-4x |